Implementation of Higher-Order Thinking Skills in Elementary School Using Learning Model, Media, and Assessment - Norma Dewi Shalikhah; Irham Nugroho (AL-ISHLAH: Jurnal Pendidikan, 2023)
The present learning process should be directed at higher-order thinking skills (HOTS). However, there are still many teachers in elementary schools who have not implemented hots learning as a whole, both in terms of learning models, media, and assessments, because there are no guidelines or modules related to the implementation of HOTS, especially at the elementary school level. This condition certainly requires an adaptation process that is not easy and also includes synthesizing, analyzing, reasoning, comprehending, applying, and evaluating. Therefore, this study aims to determine the implementation of HOTS in elementary schools, using learning models, media, and assessment. In this experiment, a narrative review was used with a database search and thematic analysis. The criteria used also emphasized the articles from various sources, such as national and international scientific journals, related topics, the last 5 years of publication within 2018-2022, and full-text pdf versions in ERIC and Mendeley. From this process, a total of 11 articles were subsequently analyzed. Based on the results, the following was obtained, (1) several learning models stimulated, trained, developed, and improved HOTS in elementary school students, using project and problem-based learning, STEM (Science, Technology, Engineering, and Mathematics), inquiry, problem determination and solution, concept construction and analysis, as well as RADEC (Read, Answer, Discuss, Explain, and Create). (2) Learning media capable of developing HOTS include question-based fun thinkers, Android-based word search educational games, and a related crossword puzzle. (3) HOTS assessments were carried out using the Two-Level Multiple Choices Test (TTMCT) instrument. This led to the establishment of the criteria for students’ product evaluations, using formative and summative assessments, self, peer, and teacher-evaluation incorporation, as well as HOTS question development. From these results, teachers need to use various learning models, media, and assessments. Teacher should also initiate the aspects of higher-order thinking skills, including learning analysis, evaluation, and development.